Pengembangan Media Bimbingan Karier Animasi Motion Graphic Sebagai Layanan Informasi Karier Pada Siswa Sekolah Dasar - Alamsyah, Muh. Nur; Umar, Nur Fadhilah; Saman, Abdul (Indonesian Journal of Educational Counseling, 2023)
This research develops career guidance media based on motion graphic animation as a career information service for elementary school students. The purpose of this research is to find out; 1) Description of media needs for career guidance; 2) Career guidance media prototype; and 3) To produce valid and practical motion graphic animation-based career guidance media. This study uses the ADDIE model. The instruments used in this study were angles and interview guidelines. Based on the results of the study, it shows that 1) Students of SD Negeri Bontocinde have a low understanding of careers so that media such as Motion graphic Animation is needed to support the implementation of career information services; 2) Prototype of Motion graphic Animation media consisting of opening, introduction, content, and outro/closing; 3) Assessment of motion graphic animation media was carried out by material experts (score 3.5 very good) and media experts (score 3.9 very good). Assessment by the teacher obtained values from all three aspects, namely usability, feasibility, and accuracy with a total proportion obtained of 84% with very valid criteria. In conclusion, the level of validity of the Animation Motion graphic media as a career information service is stated to be valid for student use so that the media is feasible for extensive testing.